Reducing Redundant Anaerobic Therapy Through Spaced Education and Antimicrobial Stewardship Interventions. (20th November 2017) - Flett, Kelly B; Bousvaros, Athos; Carpenter, Jane; Millrinen, Carly E; Martin, Patricia; Sandora, Thomas J
Abstract : Decreasing the use of redundant anaerobic therapy is a key target for antimicrobial stewardship. A short, spaced education activity, in conjunction with hospital-wide interventions, was associated with a significant reduction in the use of redundant metronidazole therapy. Abstract: Background: Decreasing the use of redundant anaerobic therapy is a key target for antimicrobial stewardship. Education techniques that optimize knowledge retention could be an important component of reducing these regimens. Methods: We implemented a quality improvement project that incorporated spaced education to reduce the use of redundant anaerobic therapy. The initial interventions (November through December 2015) included education in a hospital-wide newsletter and review of redundant anaerobic regimens by the antimicrobial stewardship program. A spaced education module was then developed with the gastroenterology (GI) service, which had a relatively high rate of redundant anaerobic therapy use. Ten questions with teaching points were delivered to GI physicians at spaced intervals over 2 to 4 weeks (February through March 2016). Knowledge scores were compared at initial and final question presentation using generalized estimating equations. Interrupted time-series analysis was used to compare the rates of redundant-metronidazole-days per 1000 patient-days among patients in the patients admitted to the GI service and those in the non-GI group before and after the intervention. Results: Of 66 GI physicians, 56 (85%) participated in the spaced education activity. After the intervention, their knowledge scores on all the questions improved, and their mean knowledge score increased from 57% to 86% ( P < .001). Nearly all (91%) of the participants were very or generally satisfied with the activity. In the GI group, the rate of redundant-metronidazole-days decreased from 26.2 to 13.0 per 1000 patient-days (relative risk [RR], 0.45 [95% confidence interval (CI), 0.27–0.73]; P = .001). This rate in the non-GI group also decreased from 5.47 to 2.18 per 1000 patient-days (RR, 0.47 [95% CI, 0.36–0.60]; P < .001) after our interventions. Conclusions: Spaced education is an effective approach for teaching antimicrobial stewardship topics. Focused provider education was associated with a sustained reduction in the use of redundant anaerobic therapy.